Kestabilan Model SIS dengan Non-monotone Incidence Rate & Treatment - Mohammad Soleh (UIN Sultan Syarif Kasim Riau, 2015)
Our paper proposed a non monoton incidence rate, logistic growth, migration, and under treatment for SIS model. The character of originally SIS model which using bilinear insience rate will cover by new model. An existences and stabilities of free disease state and endemic are investigated to explore the characteristic of model. The existence of equilibrium point is founded by solving differential equation of the model and their stability are explored by an eigen criteria. We obtained that only one free disease state and endemic which asimtotycal stable by condition.Key words: Endemic state, Free Disease state, Non Monoton Incidence Rate, SIS Model, treatment.